Facilitators of and barriers to adopting a restrictive red blood cell transfusion practice: a population-based cross-sectional survey - Soril, Lesley J.J. (CMAJ Open, 2019)
BACKGROUND: Despite recommendations for restrictive approaches to red blood cell transfusion in the intensive care unit (ICU), variation from best practices persists. The aim of this study was to explore potential facilitators of and barriers to practising a restrictive red blood cell transfusion strategy among intensive care physicians using the theoretical domains framework. METHODS: We conducted an online population-based cross-sectional survey of all intensive care physicians in 1 health care system (Alberta). Survey questions were based on 6 key theoretical domains of the theoretical domains framework: Knowledge, Social/professional roles and identity, Motivation and goals, Beliefs about consequences, Social influences and Beliefs about capabilities. The survey was administered between July 27 and Oct. 6, 2017. Descriptive statistics (demographic and Likert scale data) and conventional content analysis (open-ended responses) were conducted. RESULTS: Forty-two intensive care physicians completed the survey (estimated response rate 56%). The respondents identified knowledge of published evidence, use of guidelines, improved outcomes, physician autonomy, and perceived culture of acceptance and collegial support as facilitators of practising a restrictive transfusion strategy. Identified barriers included potential impact on and cost to other clinical goals, conflicting practices and beliefs of physicians in other clinical specialties, deficits in medical trainees’ skills and knowledge, and attitudinal barriers related to denial. INTERPRETATION: Using the theoretical domains framework, we identified 9 key self-reported facilitators of and barriers to intensive care physicians’ transfusion behaviour. Understanding these determinants will help inform development and implementation of interventions within ICUs to encourage optimal use of red blood cell transfusion practices for nonbleeding patients whose condition is stable.